Upper limb functionality and quality of life of women with breast cancer undergoing physiotherapeutic treatment - Nava, Luana Paula; Martins, Cibeli Ferreira; Lara, Simone; Ferreira, Fernanda Vargas (Journal of Health Care, 2016)
Introduction: Breast cancer is a serious public health problem and a major cause of female death in Brazil. Treatment can be surgical and/or conservativeand possible complications include lymphedema and reduced upper limb range of motion, particularly in shoulder flexion and abduction , reflecting negatively on the quality of life. Objective: Verify the impact of the application of a physical therapy protocol on functionality and quality of life of women with breast cancer. Materials and methods: An experimental (before and after) study design was used with a protocol composed of 10 sessions of scar mobilization, stretching, active-free exercises in all planes of motion in women aged between 40 and 65 years old subjected to surgery and adjuvant therapy. They were evaluated for range of motion (ROM), presence or absence of lymphedema and quality of life. Results: The sample consisted of 4 participants with mean age of 54Â±11.5, who were subjected to modified radical mastectomy and to quadrantectomy associated or not to axillary lymphadenectomy. Initially, deficits were detected in all planes of ipsilateral shoulder's movement, noticing lesser degrees of amplitude in flexion, extension, abduction and external rotation. After the protocol, we observed ROM improvement in all shoulder movements, especially in flexion and abduction. Conclusion: It was observed that a short physiotherapeutic protocol promoted shoulder ROM improvement 's and had a positive impact on the quality of life.
Keywords: breast cancer; postoperative; range of motion; quality of life; physiotherapeutic protocol